2017
DOI: 10.1007/s00453-017-0396-z
|View full text |Cite
|
Sign up to set email alerts
|

Fault-Tolerant Approximate Shortest-Path Trees

Abstract: The resiliency of a network is its ability to remain effectively functioning also when any of its nodes or links fails. However, to reduce operational and set-up costs, a network should be small in size, and this conflicts with the requirement of being resilient. In this paper we address this trade-off for the prominent case of the broadcasting routing scheme, and we build efficient (i.e., sparse and fast) faulttolerant approximate shortest-path trees, for both the edge and vertex single-failure case. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The problem of constructing multiplicative approximation replacement paths P s,t,v (i.e., such that | P s,t,v | ≤ α · |P s,t,v |) has been studied in [3,6,10]. In particular its single source variant has been studied in [4,8,21]. In this paper, we further explore this approach.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of constructing multiplicative approximation replacement paths P s,t,v (i.e., such that | P s,t,v | ≤ α · |P s,t,v |) has been studied in [3,6,10]. In particular its single source variant has been studied in [4,8,21]. In this paper, we further explore this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Parter and Peleg [19] improved this result by showing that such a subgraph exists with 3n edges. Bilò, Gualà, Leucci, and Proietti [5] showed that any weighted undirected graph has a fault tolerant (1+ )-shortest path subgraph of size O((1/ 2 )n log n). Parter and Peleg [18] showed that any unweighted (un)directed graph has a fault tolerant exact shortest path subgraph with O(n 3/2 ) edges.…”
Section: Related Workmentioning
confidence: 99%
“…For the case of multiple edge faults, Bilò et al [6] obtain a k-fault tolerant (2k+1)-shortest path subgraph with O(kn) edges again only for undirected graphs. They also showed that there is a data structure of size O(kn log 2 n) that reports the (2k + 1)-approximate distance from s in O(k 2 log 2 n) time.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations